Konstruksi Selera Remaja Putri dalam Dunia Digital - Dyanningrum Pradhikta; Ruly Darmawan; Hendy Hertiasa (Wimba : Jurnal Komunikasi Visual, 2012)
Website imaging can be built by using visual design such as layout, graphic/ image, typography and color. Website through the visual display has huge potential to form teenager disposition. Website visual display has relation which related with user perception. Teenager disposition is formed from perception to Website. Media brings certain influence to adolescent preference. Website also distribute message by audience target taste approach. Teenager curiosity and interest to website, attract teens to think and then produce disposition. Besides, website indirectly has message inside it, whcih is a metaphor of lifestyle room, consumption and taste. Media capacity included in taste conditioning, which is, website gives offers through choices, not just information content displayed, but also via various visual display. In that time, this variety will be construct taste.